Regeneration of Ni/Al2O3 catalyst in CO2 methanation - Rima Melati; Robert Junaidi; Mustain Zamhari (Universitas Lambung Mangkurat, 2024)
CO₂ emissions are one form of greenhouse gas (GHG) emissions that contribute to global warming. CO₂ contributed 175.62 million tons in 2021, impacting greenhouse gas levels. One strategy to reduce the concentration of CO₂ in the atmosphere is to convert CO₂ gas into useful chemicals. One example of this is the hydrogenation of CO₂ to produce methane, which can serve as an alternative to LPG. The aim of this research is to produce methane gas by developing a fixed bed reactor in a simple manner. The catalyst Ni/Al2O3 with 20 grams and five regenerations could produce CH₄ up to 49.73% compared to 39.06% for those with 10 grams. However, the H2 gas remaining is higher for those with 10 grams (1.454 ppm compared to 1.042 ppm). Also, The CO2 gas remaining is higher for those with 10 grams (58.18% compared to 47.92%). The results of this study can be the basis for developing energy policies, encouraging investment in clean energy technologies, and supporting the reduction of greenhouse gas emissions for energy sustainability and resilience.